Valproic acid induces histologic changes and decreases androgen receptor levels of testis and epididymis in rats - Sitthichai Iamsaard; Wannisa Sukhorum; SupatchareeArun; Nichapa Phunchago; Nongnuch Uabundit; Porntip Boonruangsri; Malivalaya Namking (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Valproic acid (VPA), an anti-epileptic drug, can cause male subfertility. However, the degree to which testicular and epididymal histopathologies and androgen receptor (AR) expression are changed under VPA treatment has never been reported. Objective: To investigate the histopathological changes and AR protein levels of testis and epididymis in VPA-treated rats for every single day. Materials and Methods: Sixty-four adult male Wistar rats were divided into control and VPA-treated groups (n=8/ each). Treated rats were injected with 500 mg/ kgBW, intraperitoneally, VPA for 10 consecutive days. At the end of every experimental day, all reproductive parameters including histology by hematoxylin and eosin staining and protein expression of AR by Immuno-Western blot in testis and epididymis were examined. Results: VPA-treated rats showed dramatically changes in testicular and epididymal histopathologies compared to control group. The multinucleated giant cells and sloughing of germ cells were observed on day 6. The germ cell disintegration and increased intercellular spaces of seminiferous tubular epithelium appeared in days 7-10 of VPA treatment. Additionally, extensive multinucleated giant cells and complete exfoliation were clearly found from days 8-10. Such exfoliated germ cells were clearly seen in its epididymal lumen at day 10. The increasing rate of sperm concentration was approximately 32.31% of that in control group at day 10 (p=0.03). Moreover, the protein expressions of testicular and epididymal AR (% intensity/ 80 μg protein lysate) was decreased in VPA-treated rats compared with control. Conclusion: VPA treatment induces histologic changes of germ cell epithelium in seminiferous tubules and decreases the expression of testicular and epididymal androgen receptors